A semismooth Newton method for nonlinear symmetric cone programming - Kong, Lingchen; Meng, Qingmin (Mathematical methods of operations research (Heidelberg, Germany), 2012)
In this paper, we employ the projection operator to design a semismooth Newton algorithm for solving nonlinear symmetric cone programming (NSCP). The algorithm is computable from theoretical standpoint and is proved to be locally quadratically convergent without assuming strict complementarity of the solution to NSCP.